A hybrid cascaded multilevel inverter application for renewable energy resources including a reconfiguration technique - Khomfoi, S; Praisuwanna, N; Tolbert, L M (2010 IEEE Energy Conversion Congress and Exposition, 2010)
A hybrid cascaded multilevel inverter application for renewable energy resources including a reconfiguration technique is developed. The objective of this research is to propose an alternative topology of hybrid cascaded multilevel inverter applied to a low voltage dc microgrid in telecommunication buildings. The modified PWM technique is also developed to reduce switching losses. Also, the proposed topology can reduce the number of required power switches compared to a traditional cascaded multilevel inverter. A possible reconfiguration technique after faulty condition is also discussed. PSIM (PowerSim) and Simulink/MATLAB are used to simulate the circuit operation and control signal. A 3-kW prototype is developed. The switching losses of the proposed multilevel inverter are also investigated. By using the modified PWM technique and reconfiguration method, the proposed hybrid inverter can improve system efficiency and reliability. The proposed inverter efficiency is 97% under tested condition. The results show that proposed hybrid inverter topology is a promising method for a low voltage dc microgrid interfacing with renewable energy resources.